From normativity to responsibility - Raz, Joseph (Oxford : Oxford University Press, 2011)
What are our duties or rights? How should we act? What are we responsible for? Joseph Raz examines the philosophical issues underlying these everyday questions. He explores the nature of normativity - the reasoning behind certain beliefs and emotions about how we should behave - and offers a novel account of responsibility.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Responsibility; Normativity (Ethics)